Theoretical determination of energies, wavelengths, and transition probabilities for EUV and SXR spectral lines in Rb XXXIV, Sr XXXV, Zr XXXVII, and Nb XXXVIII. (March 2019) - Chen, Zhan-Bin; Sang, Cui-Cui; Wang, Kai
Highlights: Excitation energies, transition wavelengths, and transition probabilities for EUV and SXR spectral lines in Rb XXXIV, Sr XXXV, Zr XXXVII, and Nb XXXVIII are reported. The most accurate and complete, as of today, atomic data for Rb XXXIV, Sr XXXV, Zr XXXVII, and Nb XXXVIII are provided. The present work should be useful for diagnostics of hot plasmas in fusion applications. Abstract: Energy levels, radiative processes and lifetimes are studied among the 98 lowest levels of the 1 s 2 2 snl and 1 s 2 2 pnl ( n = 2–4, l = 0–3) configurations of Rb XXXIV, Sr XXXV, Zr XXXVII, and Nb XXXVIII. The GRASP2K (General-purpose Relativistic Atomic Structure Package) is adopted, in which the orbital set is systematically expanded within the orbital space up to n = 9, and the Breit interaction and leading quantum electrodynamical corrections are considered. Results are provided for four types of transitions:electric dipole, electric quadrupole, magnetic dipole, and magnetic quadrupole. Similar data for the 166 lowest states belonging to the n ≤ 5 configurations are also determined using the second-order relativistic many-body perturbation theory to assess the accuracy of the calculations, taking Sr XXXV as an example. Good agreement is found between results of this work and available values from the Atomic Spectra Database of the National Institute of Standards and Technology and other theoretical reports. The accuracy for energies and radiative rates is estimated to be about 0.02% and 5%, respectively. These accurate theoretical data can aid line identifications in extreme ultraviolet (EUV) and soft X-ray (SXR) spectra. The present work should be useful for diagnostics of hot plasmas in fusion applications.